The Effect of Different Pure Natural Honey On Betta Fish Seed Production (Betta splendens) Male - Gumelar, Tedi; Rina, Rina; Farkan, Mochammad; Zaidy, Azam B. (Syiah Kuala University, 2025)
Only around 40% of male betta fish are typically produced under normal conditions. Honey, a natural substance containing potassium and flavonoids, has the potential to alter fish sexuality from female to male. Potassium plays a key role in regulating testosterone and supporting androgen function, which promotes male characteristics in fish. This study aimed to identify the type of pure natural honey that most effectively increases the production of male betta fish fry. A completely randomized design (CRD) was used, consisting of four treatments with three replications each. The treatments were: (1) control (no honey soaking), (2) soaking eggs in Forest honey solution at a dose of 5 mL/L, (3) soaking eggs in Multiflora honey solution at 5 mL/L, and (4) soaking eggs in Randu honey solution at 5 mL/L. Sex identification was carried out at 60 days through morphological observation of the urogenital organs, and confirmed at 70 days using gonad histology with hematoxylin-eosin (HE) staining. The results showed that the highest percentage of males was obtained in Treatment 3 (Multiflora honey), at 59.59% 1.65, while the lowest was in the control group (Treatment 1) at 43.30% 1.70. The survival rate differed significantly among treatments, ranging from 40.00% to 66.67%, and the hatching rate ranged from 70% to 90%. Water quality parameters including temperature, pH, and dissolved oxygen (DO) remained within the optimal range for betta fish maintenance throughout the study. In conclusion, Multiflora honey was the most effective in increasing the production of male betta fish fry.